2014
DOI: 10.1249/mss.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Mediated Dilation in Athletes

Abstract: The current meta-analysis provides evidence that master athletes but not young athletes exhibit greater FMD compared with that in age-matched healthy controls, thus suggesting that the association between high levels of exercise training and increased FMD is age dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 58 publications
(118 reference statements)
6
28
4
Order By: Relevance
“…Our finding does not confirm the results presented in a recent meta-analysis [23], which indicated that greater FMD values in athletes were observed in master athletes but not in subgroup of young athletes. The population investigated in our study constituted young athletes at age of less than 40 years.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding does not confirm the results presented in a recent meta-analysis [23], which indicated that greater FMD values in athletes were observed in master athletes but not in subgroup of young athletes. The population investigated in our study constituted young athletes at age of less than 40 years.…”
Section: Discussioncontrasting
confidence: 99%
“…Together, our results indicate a lack of association of ADMA and any of the L-arginine analogue concentrations with the ability for O 2 muscle delivery and extraction in healthy subjects. These results provide additional support to the hypothesis that, in healthy subjects, interindividual differences inV O 2 max may not be related to any differences in endothelium-dependent vasodilatation (Montero et al, 2014. Indeed, exercise capacity is significantly associated with endothelial function in less than 50% of studies in healthy subjects after adjustment for age (Montero, 2015).…”
Section: Discussionsupporting
confidence: 70%
“…These results provide additional support to the hypothesis that, in healthy subjects, interindividual differences inV O 2 max may not be related to any differences in endothelium-dependent vasodilatation (Montero et al, 2014. These results provide additional support to the hypothesis that, in healthy subjects, interindividual differences inV O 2 max may not be related to any differences in endothelium-dependent vasodilatation (Montero et al, 2014.…”
Section: Discussionsupporting
confidence: 69%
“…Missing standard deviations (SD) of RBCV, PV, and BV were imputed from linear regression analysis of log(SD of RBCV, PV, or BV) on log(mean RBCV, PV, or BV) from studies that reported complete data, as previously described (Marinho et al., ). A systematic appraisal of quality for observational research (SAQOR) (Ross et al., ), previously applied in meta‐analysis of observational studies evaluating the effect of ExT (Montero et al., , ,b,c), was performed to provide assessment of study quality. The SAQOR was adjusted to assess (a) the study sample, (b) quality of blood volumes assessment, (c) confounding variables, and (d) data.…”
Section: Methodsmentioning
confidence: 99%